PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE QUALITY TERHADAP MANAJEMEN LABA - FERRY SUHARDJO; MICHELLE CESRYN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence and to analyze the effect of form size, leverage, firm age, corporate governance quality, growth and profitability on earnings management. The population of this research are non-financial companies that listed in Indonesia Stock Exchange (IDX) during the period of 2017-2019. The sample used in this study are 573 data from 193 non-financial companies that has been listed in Indonesia Stock Exchange (IDX)selected using by purposive sampling method. In this study, the hypotheses were tested and analyzed by purposive sampling method with Statistical Product and Service Solution (IBM SPSS) application tool. The result of this research indicate that the variable growth have influence on earnings management, while the variable of firm size, leverage, firm age, corporate governance quality, profitability have no influence on earnings management